THE TRANSLATION OF GESTURES AND BODY LANGUAGESТ IN THE NOVEL “DAYS GONE BY” BY ABDULLA KADIRI (Scientific journal of the Fergana State University, 2023)
The description of actions in “Days gone by” by Abdulla Kadiri and their translation into German and Russian. I was discussea Some minor in translation was aslo mentioned.